1-methyl-1-phenyl-3-(phthalimidoacetyl)cyclobutane - Özdemir, N; Dinçer, M; Yilmaz, I; Cukurovali, A (Int Union Crystallography, 2004)
The title molecule, C21H19NO3, consists of three essentially planar fragments. There is negligible puckering in the cyclobutane ring. The crystal structure is stabilized not only by weak intermolecular C-H...O hydrogen-bond interactions but also by weak C-H...pi(ring) interactions, with an H...Cg distance of 2.85 Angstrom (where Cg is the centroid of the phthalimido six-membered ring).
Keywords: Crystal-Structure; Thalidomide